Improving PPKN Learning Outcomes using Audio Visual Media - Noviyanti, Dwi Ganis (Universitas Sebelas Maret, 2020)
The use of appropriate media in the teaching and learning process will create a pleasant learning atmosphere. In the teaching and learning process, teachers are expected to provide teaching that is easily understood by students. One of the learning media that can be used to improve learning outcomes of PPKN subjects in the precepts of Pancasila is audio visual media. This research is a classroom action research conducted in three cycles consisting of the stages of planning, action, observation, and reflection. Data obtained from teacher observations in managing learning, observations of student activities in the learning process, and student learning test results. The data analysis technique used is quantitative techniques. The results showed that the students' learning outcomes using audio-visual media in the first cycle had an average value of 76. In the second cycle the average value was 84 and in the third cycle the average value was 86. Based on the results of data analysis, it can be concluded that the use of audio media visuals are very suitable for use in learning and can improve learning outcomes.